Compact true time delay line with partially shielded coplanar waveguide transmission lines - Lim, Hong Yi (2013)
This paper presents a method to attain a compact true time delay line with a partially shielded coplanar waveguide transmission line. Closely spaced air bridges were utilized to reduce the coupling effects between neighboring coplanar waveguide transmission lines. The proposed method is compatible with foundry's GaAs standard process and allows the transmission line to be compact and achieve a small sized true time delay line circuit. A true time delay line of approximately 85ps was fabricated and tested.